Thoracoscopy pulmonary biopsy by two portals with a novel pre-tied loop ligature device in rabbits: an experimental study - Wittmaack, Monica Carolina Nery [UNESP]; Sembenelli, Guilherme; Conceição, Maria Eduarda Bastos Andrade Moutinho da [UNESP]; Montanhim, Gabriel Luiz [UNESP]; Crivellaro, Roberta Martins [UNESP]; Rolemberg, Daniele Santos [UNESP]; Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Silva, Marco Augusto Machado da; Teixeira, Pedro Paulo Maia; Moraes, Paola Castro [UNESP] (Universidade Federal de Santa Maria, 2022)
Thoracoscopy is replacing open lung biopsies because it is less invasive, usually the technique is done using three portals and intracorporeal suture technique. This study described the feasibility and efficacy of a novel pre tied loop ligature and to propose a thoracoscopic access strategy with two portals to perform lung biopsy in patients under 5 kg. Ten rabbits were positioned in dorsal recumbency. Total thoracoscopic lung biopsy was performed using a combined transdiaphragmatic approach and a right intercostal approach. A pre tied loop ligature was placed to perform a caudal lung lobe biopsy. Insufflation of the thoracic cavity was not performed. The total surgery time was 41.4 ± 14.5 min. The procedure was carried out free of complications that prevented slippage or tightening the knot or that made it come loose after the lung biopsy; there was no serious complication during the surgical procedure. The samples obtained averaged 1x0.64x0.45 cm (Length, Width, Depth) and were considered satisfactory according to the histopathologic evaluation. Thorax radiographs taken before and after the surgeries were compared and showed no pneumothorax or hemothorax. Necropsy confirmed no knot failure occurred at the biopsy site. The use of the novel pre tied loop ligature is a safe and effective technique, avoiding problems with the limited size of the thoracic cavity in small patients.

A toracoscopia está substituindo as biópsias pulmonares abertas por ser menos invasiva. Usualmente a técnica é feita utilizando três portais e ligaduras feitas intra corporalmente. O objetivo deste estudo foi descrever a viabilidade e eficácia de uma nova ligadura com alça pré-amarrada e propor uma estratégia de acesso toracoscópico com dois portais para realizar biópsia pulmonar em pacientes com menos de 5kg. Dez coelhos foram posicionados em decúbito dorsal. A biópsia pulmonar por toracoscopia total foi feita pela abordagem combinada transdiafragmática e abordagem intercostal direita. Uma nova ligadura pré-amarrada foi colocada para realizar uma biópsia do lobo pulmonar caudal. Não foi realizada insuflação da cavidade torácica. O tempo total de cirurgia foi de 41,4 ± 14,5 min. Os procedimentos foram realizados sem complicações que impedissem o escorregamento ou aperto do nó ou que o soltassem após a biópsia pulmonar; não houve nenhuma intercorrência grave durante o procedimento cirúrgico. As amostras coletadas tinham tamanho médio 1x0,64x0,45 cm e foram consideradas satisfatórias de acordo com a avaliação histopatológica. As radiografias de tórax feitas antes e depois das cirurgias foram comparadas e não mostraram pneumotórax ou hemotórax. A necropsia confirmou que não ocorreu falha do nó no local da biópsia. Conclui-se que uso da nova ligadura com alça pré-amarrada é uma técnica segura e eficaz, evitando problemas com o tamanho limitado da cavidade torácica em pacientes pequenos.
Biópsia pulmonar por toracoscopia por dois portais com uma nova ligadura de alça pré-amarrada em coelhos: um estudo experimental
Keywords: endoloop; lung biopsy; small patients; thoracic surgery; transdiaphragmatic thoracoscopy and videosurgery; biópsia pulmonar; cirurgia torácica; endoloop; pequenos animais; toracoscopia transdiafragática e videocirurgia